Clinical epidemiological characterization of patients operated on cephalic pancreaticoduodenectomy with disease of the biliopancreatic confluent - Danilo Romaguera Barroso; José Alejandro Gutiérrez Aguller; Oriol Valón Costa; Ana Lubín García; Liuvok Pratt Pérez Urdanet (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The cephalic pancreaticoduodenectomy continues being a complex surgical intervention.   Objective: To characterize patients operated on cephalic duodenopancreatectomy according to selected epidemiological, clinical and histologic variables.  Methods: An observational, descriptive and retrospective study of a series of 15 cases operated on cephalic pancreaticoduodenectomy was carried out in the General Surgery Service of Saturnino Lora Teaching Provincial Hospital in Santiago de Cuba, during the five year period 2016-2020.  The analyzed variables were age, sex, comorbidities, toxic habits, symptoms and signs, as well as histologic type of the lesions.  Results: There was a prevalence of the male sex patients (80.0 %) and the 50 to 55 age group (40.0 %). The most frequent comorbidities were hypertension in 80.0 % of the case material, followed by the diabetes mellitus in 53.3 %. Nicotine addiction (66.7 %) and alcoholism (60.0 %) prevailed, as well as the signs of biliary obstruction (73.3 %). The main histologic diagnosis was pancreas adenocarcinoma in 60.1 % of those affected.   Conclusions: The cephalic pancreaticoduodenectomy is carried out predominantly in patients with pancreas adenocarcinomas and, to a lesser extent, in patients with duodenum adenocarcinomas and other benign affections; in those affected of the male sex, with intermediate and advanced ages of life, hypertension and diabetes mellitus, as well as long time of being smokers and alcohol consumers. The signs of biliary obstruction are of capital importance in the clinical diagnosis.